2022
DOI: 10.55230/mabjournal.v51i4.08
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect of Dillapiole on Human Breast Cancer McF-7 Cells

Abstract: Plant secondary metabolites and their derivatives play a significant role in anticancer drug therapy since they are effective against specific characteristics while reducing side effects. Dillapiole is a phenylpropanoid that holds several bioactivities like anti-fungal, anti-inflammatory, anti-leishmanial, and anti-cancer. This study aims to investigate the possible cytotoxic effect of dillapiole on human breast cancer, MCF-7 cells. Cells were cultured in complete RPMI media and incubated at standard culture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The antifungal activity of dillapiol has also been investigated, and it has been reported that dillapiol is characterized by antifungal properties against pathogenic fungal strains [ 32 ]. Other studies have reported that dillapiol exerts cytotoxic activity against a wide range of tumor cells by stimulating ROS production, leading to cell apoptosis [ 45 , 46 , 47 ]. Scholars have suggested that dillapiol has antiparasitic activity against parasites of the genus Leishmania [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antifungal activity of dillapiol has also been investigated, and it has been reported that dillapiol is characterized by antifungal properties against pathogenic fungal strains [ 32 ]. Other studies have reported that dillapiol exerts cytotoxic activity against a wide range of tumor cells by stimulating ROS production, leading to cell apoptosis [ 45 , 46 , 47 ]. Scholars have suggested that dillapiol has antiparasitic activity against parasites of the genus Leishmania [ 48 ].…”
Section: Resultsmentioning
confidence: 99%